HARKAT DAN MARTABAT MANUSIA DALAM PANDANGAN KENEGARAAN PANCASILA DAN UUD NRI TAHUN 1945 - Suroto Suroto (Jurnal Pembaharuan Hukum, 2015)
The formulation of Pancasila is constitutionally contained in the fourth paragraph of the preamble of the 1945 Constitution. The human dignity and purity in Pancasila's view which means the values of Pancasila arise and is extracted from the thinking of Indonesian philosophy, and contains spiritual values in accordance with the Indonesian people's conscience. The state of Pancasila essentially contains a concept of principle and value that is used as the source of all elaboration of legal norms up to other norms. According to the 1945 Constitution is the parent of the highest state law, this subject is contained in Chapter XA of Article 28-28J, that the state will always guarantee and protect all human rights and dignity wholly owned without diminished, when and where even the protection of human rights and dignity is always put on top of all other needs.